Singular perturbation methodology in control systems - Naidu, D. S. (Desineni S.) 1940- (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
This book presents the twin topics of singular perturbation methods and time scale analysis to problems in systems and control. The heart of the book is the singularly perturbed optimal control systems, which are notorious for demanding excessive computational costs. The book addresses both continuous control systems (described by differential equations) and discrete control systems (characterised by difference equations).
Electronic reproduction.
Keywords: Automatic control -- Mathematical models; Control theory -- Mathematical models; Perturbation (Mathematics); Electronic books